2019
DOI: 10.1186/s12974-019-1611-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and anti-inflammatory effects of probiotics in multiple sclerosis: a systematic review

Abstract: Multiple sclerosis (MS) is an inflammatory and autoimmune neurological disorder which leads to demyelination. Although the etiology of MS is yet to be known, it appears that regulating the immune system and suppressing inflammatory pathways may possibly have a favorable effect on the healing of this disease. Evidence suggests that probiotics consumption via gut microbiome alteration devises beneficial effects in improving immune and inflammatory responses in MS. All articles were systematically searched (in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 79 publications
2
59
0
1
Order By: Relevance
“…Probiotics refer to live bacteria that are beneficial to the host when ingested at an appropriate amount [ 7 ]. They have been known for their intestinal effects [ 6 ], but recently, their function has been known to be extended to strengthening the immune system, reducing cholesterol level, enhancing vaginal health, and improving skin health [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics refer to live bacteria that are beneficial to the host when ingested at an appropriate amount [ 7 ]. They have been known for their intestinal effects [ 6 ], but recently, their function has been known to be extended to strengthening the immune system, reducing cholesterol level, enhancing vaginal health, and improving skin health [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of pathology and etiology of MS have not been dissolved yet, but evidence has presumed that immunomodulatory and anti-inflammatory treatments can delay MS development. According to the prior note, it has been suggested that vitamin D 3 can have a major role in immune regulation in MS [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D 3 has a probable immune-modulatory effect which, changes the equilibrium between anti-and pro-inflammatory interleukins in favor of anti-inflammatory cytokines. So, the lack of vitamin D 3 is possible to cause inflammatory situations in MS patients [2,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies support the rationale development of novel probiotics for the treatment of MS. The pivotal importance of immunomodulatory IL-10, IL-35, Tregs, and metabolites, such as SCFA and neurotransmitters, and other protective factors identified in these animal models and clinical studies will provide insight into the development of novel therapeutic targets for use in genetically engineered probiotics [ 165 ]. Figure 1 depicts the mechanisms of action proposed for probiotics that could result in the control of neuroinflammation-mediated demyelination.…”
Section: Interventions Of the Intestinal Microbiota As A Treatmentmentioning
confidence: 99%